2001
DOI: 10.1046/j.1439-0388.2001.00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of (co)variance component estimates in control populations of red flour beetle (Tribolium castaneum) using restricted maximum likelihood and Gibbs sampling

Abstract: Bayes Analyse in der Implementierung mit Gibbs sampling ermo È glicht. Generell konnte festgestellt werden, dass das 95%ige Zentralintervall der Scha Ètzungen unter den drei Gewichtungen in den Populationen denen der Kontrolllinien a Èhnlich war. Die meisten REML Scha Ètzer in den Basispopulationen unterscheiden sich von den REML Scha Ètzern in den Kontrolllinien. Unzureichende Informationen aus den Daten und confounding der zufa Èlligen Effekte trugen zur Variabilita Èt der REML Scha Ètzungen in den Basispopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…However, other simulation studies also suggested that the choice of priors could have a considerable influence on the result of Bayesian method (e.g. Lin and Berger, 2001). Consequently, additional simulation studies of effect for different priors on the individual model are carried out to determine the proper one.…”
Section: Introductionmentioning
confidence: 99%
“…However, other simulation studies also suggested that the choice of priors could have a considerable influence on the result of Bayesian method (e.g. Lin and Berger, 2001). Consequently, additional simulation studies of effect for different priors on the individual model are carried out to determine the proper one.…”
Section: Introductionmentioning
confidence: 99%